STRATEGI PENGEMBANGAN PERIKANAN TANGKAP DI KABUPATEN SUMBAWA BARAT - Muhammad Nursan; Dudi Septiadi (Jurnal Bisnis Tani, 2022)
Capture Fisheries is an agricultural sub-sector that has great potential to be developed in West Sumbawa Regency, however, there are still problems faced that need to be solved in order to develop capture fisheries and improve fishermen's welfare. The purpose of this study is to formulate a capture fisheries development strategy in West Sumbawa Regency. The research was conducted in Taliwang and Poto Tano districts which were selected by purposive sampling because it is the area with the highest number of fishers in West Sumbawa Regency. Research respondents were determined as many as 30 people consisting of fishermen and stakeholders in the field of capture fisheries. The method used in this research is descriptive research method. Research data were collected using survey techniques through direct interviews guided by the research questionnaire. Then the data collected was analyzed using SWOT analysis to formulate a capture fisheries development strategy. From the results of the SWOT analysis, it is found that the chosen strategy is the S-O (Strength–Opportunity) strategy, which is a strategy that optimizes strengths to seize opportunities. The SO strategy formulation includes expanding the market by conducting processing to create added value and competitiveness of capture fisheries products, developing the use of appropriate, effective, efficient and environmentally friendly capture fisheries technology, and optimizing the role of government and institutions to increase production and implementation of development policies on sustainable capture fisheries.